Characteristics of Anosmia Cases in Covid-19 Patients: A Systematic Review - Sulistyani, S; Winarsih, Danik Sri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2020)
Introduction: Anosmia is one of the clinical neurological manifestations in Covid-19 patients and is an important clue in the diagnosis of Covid-19. These symptoms can occur in the early stages of Covid-19 disease. The characteristics of anosmia in covid-19 patients are not widely known, therefore a study is needed to be able to understand the overall picture of Covid-19 patients with anosmia symptoms. This information can be used as a screening and diagnosis of Covid-19 in order to get immediate treatment, so that the cure rate increasesPurpose: to determine the characteristics of anosmia cases in COVID-19 patientsMethodology: This study used database sources from the Pubmed and Science Direct, using keywords (“severe acute respiratory syndrome coronavirus 2” OR “severe acute respiratory syndrome coronavirus 2” OR “ncov” OR “2019-nCoV” OR “COVID-19” OR “SARS-CoV-2”) AND (“olfaction disorders” OR Anosmia). This research had an ethical clearance provision from Ethical Clearance Committee FK UMS No 3096./C.1/KEPK-FKUMS/XI /2020.Results: the mean age of anosmia was 47.5 years and was more prevalent in women. The average full recovery time was 21 days, the most comorbid in cases of anosmia was hypertension, and nasal congestion was the most comorbid nasal symptom in cases of anosmia.Conclusion: Based on characteristic age, sex, symptoms of anosmia, nasal congestion in young women with various comorbidities, and especially hypertension, can be considered for screening cases of Covid-19.Applications/Originality/Value: This research can be used as information to the public about the characteristics of anosmia and can find out the factors that can affect someone infected with Covid-19. Previous publications on anosmia have not fully discussed the characteristics of anosmia, but in this study the characteristics of anosmia are quite completely discussed.